Cover Feature: Laying Waste to Mercury: Inexpensive Sorbents Made from Sulfur and Recycled Cooking Oils (Chem. Eur. J. 64/2017). Issue 64 (12th September 2017) - Worthington, Max J. H.; Kucera, Renata L.; Albuquerque, Inês S.; Gibson, Christopher T.; Sibley, Alexander; Slattery, Ashley D.; Campbell, Jonathan A.; Alboaiji, Salah F. K.; Muller, Katherine A.; Young, Jason; Adamson, Nick; Gascooke, Jason R.; et al.
Abstract : With the Minamata Convention coming into force this year, there is a growing requirement for low‐cost sorbents for mercury pollution. Thus, a polysulfide was prepared by the co‐polymerization of sulfur and canola oil. As sulfur is a byproduct of the petroleum industry and used cooking oils are suitable starting materials, the resulting sorbent can be prepared entirely from waste. This high‐sulfur rubber was effective in trapping diverse forms of mercury including mercury metal, inorganic mercury, and organomercury compounds. More information can be found in the Full Paper by J. M. Chalker et al. onpage 16219 .